(untitled) (European Journal of Pure and Applied Mathematics, 2025)
This paper presents a new class of functions called weakly contra-(τ_1,τ_2)-continuous functions. Moreover, several characterizations and some properties concerning weakly contra-(τ_1,τ_2)-continuous functions are established.